2015
DOI: 10.1177/2055102915598676
|View full text |Cite
|
Sign up to set email alerts
|

Self-determination and gender–power relations as predictors of condom use self-efficacy among South African women

Abstract: This article identifies correlates of condom use self-efficacy using concepts from self-determination theory and gender–power measures. A cross-section of Xhosa-speaking women (n = 238) from Eastern Cape, South Africa, was used to conduct bivariate correlations and multivariate linear regression analyses. Gender equality beliefs and HIV knowledge were positively associated with condom use self-efficacy generally and in risky situations. Condom use self-efficacy generally was also positively associated with pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 67 publications
2
12
0
Order By: Relevance
“…49 Conversely, these studies showed that participants who experienced a lack of social support were more efficacious to use condoms and that a low level of social support was associated with sexual risk taking. 50,51 A possible strategy for maximizing selfefficacy for condom use would be to take a social-cognitive approach that involves creating a positive social environment that gives cues about acceptable behavior. This tactic could be included within an approach that emphasizes observational learning and skill-building.…”
Section: Discussionmentioning
confidence: 99%
“…49 Conversely, these studies showed that participants who experienced a lack of social support were more efficacious to use condoms and that a low level of social support was associated with sexual risk taking. 50,51 A possible strategy for maximizing selfefficacy for condom use would be to take a social-cognitive approach that involves creating a positive social environment that gives cues about acceptable behavior. This tactic could be included within an approach that emphasizes observational learning and skill-building.…”
Section: Discussionmentioning
confidence: 99%
“…This article reports on a component of baseline data that were collected as part of a randomized-controlled trial (Mpondo, Ruiter, van den Borne, Reddy, 2015). From September 2012 to March 2013, participants were recruited from the OR Tambo and Amathole district municipalities of the Eastern Cape Province, South Africa; both districts lie along the Eastern seaboard of the Indian Ocean.…”
Section: Methodsmentioning
confidence: 99%
“…Self-regulation reflects an individual's capacity to override a well-learned "dominant" response or a response that is strongly linked to impulses, urges, and cravings that are often reinforced by intrinsic reward (e.g., sensations of pleasure through dopaminergic pathways in the brain) Inzlicht, Schmeichel, & Macrae, 2014). Many health-related behaviors such as healthy eating, physical activity, quitting smoking, reducing alcohol consumption, and condom use require an individual to forego the short-term rewards related to engaging in the undesired health-compromising behavior, in favor of longer-term desired outcomes such as psychological well-being and quality of life (Hagger, Leung, et al, 2013;Hagger, Panetta, et al, 2013;Mpondo, Ruiter, van den Borne, & Reddy, 2015;Muraven & Shmueli, 2006). There are numerous perspectives on self-regulation; many view self-regulation as an individual difference, an enduring trait that increases individuals' capacity to pursue long-term goals over short-term gain in multiple domains (Allom, Panetta, Mullan, & Hagger, 2016;de Ridder, Lensvelt-Mulders, Finkenauer, Stok, & Baumeister, 2012).…”
Section: Emotion Self-determination and Self-regulationmentioning
confidence: 99%